Comparison of serum amylase level between dipeptidyl peptidase-4 inhibitor and GLP-1 analog administration in patients with type 2 diabetes mellitus - Junichi Okada; Eijiro Yamada; Yawara Niijima; Shuichi Okada; Masanobu Yamada (BMC, 2019)
Abstract We monitored serum amylase level in patients with type 2 diabetes mellitus (T2DM) prescribed either dipeptidyl peptidase-4 inhibitor or GLP-1 analog (GLP-1 group) as monotherapy. Patients were treated for a 36-month period. All subjects were non-smoker and did not take any alcoholic beverages. Forty-nine patients were prescribed DPP4is (DPP4i group), and 9 patients were prescribed GLP-1 analogs (GLP-1 group). The median of serum amylase levels in DPP4is group was 73 U/mL and the median of serum amylase levels in GLP-1 analog group was 76. Thus, there was no statistical significance between the two groups. However, the increased serum amylase levels in the three patients were observed only in the DPP4is group. One strength of the current study is that the serum amylase level was consistently measured in all subjects, and those subjects had been treated with either DPP4is or GLP-1 analogs as monotherapy. The incidence of elevated serum pancreatic amylase levels beyond normal range was calculated as 6.12% in the DPP4is group although the frequency was 0% in the GLP-1 analog group. Measurement of serum amylase consistently might have clinical meaning to catch the onset of pancreatitis and minimize the side effects due to DPP4is and GLP-1 analogs.